Sensitivity Analysis of Correlation Distance (R) Parameter Value to PGA Value by Using PSHA Method - Sandi, Kurnia; Hutagaol, Agnes Glory Emanuela; Syahbana, Arifan Jaya (Himpunan Ahli Teknik Tanah Indonesia, 2025)
Indonesia is one of the countries prone to earthquakes due to its geographical condition, which is located at the confluence of three main tectonic plates: the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate. In the context of earthquakes, the terms correlation distance and PGA (Peak Ground Acceleration) are known. Problems in correlation distance (R) only exist in background source earthquakes because of the Smoothed Gridded Seismicity process. PGA is a measure of the maximum ground acceleration that occurs during an earthquake. PGA is used in earthquake engineering to assess the potential damage that may be caused by an earthquake. Therefore, it is necessary to conduct research to determine the effects of the correlation distance parameter (R) on the PGA value using USGS PSHA software. The data used in this study are background earthquake data obtained from the National Earthquake Center Catalog (PuSGeN) in 2017. The research locations include Banten, Lampung, Southeast Sulawesi, West Sumatra, Gorontalo, and Bali. These locations were chosen because of their geographical conditions which are located near or around tectonic plates, making them prone to earthquakes. This research utilizes several modules from the USGS PSHA, namely AgridMLsm, HazgridXnga2, and HazallXL to process background earthquake data using ArcMap software from ArcGIS. The correlation distance (R) used in this study is 25, 50, 75, and 100 km. From the six provinces used as research locations, it is concluded that the difference in distance affects the resulting PGA values. In general, the greater the correlation distance value, the greater the PGA value. However, there are some points where the smaller the correlation distance, the larger the PGA value because these points are close to many earthquake sources.